Industrial Application of Nanocelluloses in Papermaking: A Review of Challenges, Technical Solutions, and Market Perspectives - Ana Balea; Elena Fuente; M. Concepcion Monte; Noemi Merayo; Cristina Campano; Carlos Negro; Angeles Blanco (Molecules, 2020)
Nanocelluloses (NC) increase mechanical and barrier paper properties allowing the use of paper in applications actually covered by other materials. Despite the exponential increase of information, NC have not been fully implemented in papermaking yet, due to the challenges of using NC. This paper provides a review of the main new findings and emerging possibilities in this field by focusing mainly on: (i) Decoupling the effects of NC on wet-end and paper properties by using synergies with retention aids, chemical modification, or filler preflocculation; (ii) challenges and solutions related to the incorporation of NC in the pulp suspension and its effects on barrier properties; and (iii) characterization needs of NC at an industrial scale. The paper also includes the market perspectives. It is concluded that to solve these challenges specific solutions are required for each paper product and process, being the wet-end optimization the key to decouple NC effects on drainage and paper properties. Furthermore, the effect of NC on recyclability must also be taken into account to reach a compromise solution. This review helps readers find upscale options for using NC in papermaking and identify further research needs within this field.